Outcomes of Reference Pricing for Angiotensin-Converting–Enzyme Inhibitors - Schneeweiss, Sebastian; Walker, Alexander M; Glynn, Robert J; Maclure, Malcolm; Dormuth, Colin; Soumerai, Stephen B (The New England journal of medicine, 2002)
Reference pricing is a potential cost-control mechanism for prescription drugs. For medications within a specific class, health insurance typically covers the cost up to the reference price. For more expensive medications, patients pay the extra cost. This study examined the effects of reference pricing for angiotensin-converting–enzyme inhibitors, which was introduced in British Columbia, Canada, in January 1997. It found little evidence that patients stopped treatment or that health care utilization or costs increased. In the United States, $117 billion — that is, 8.9 percent of overall health care expenditures — was spent for prescription drugs in 2000. 1 Drug expenditures grew 2.5 to 3 times as fast as total health care expenditures between 1998 and 2000 1 – 3 and are about to exceed hospital expenditures for some health plans. 4 Recently, reference pricing has been suggested as a cost-control mechanism for proposed Medicare drug benefits. 5 Reference pricing is based on the assumption that medications within a specific class are interchangeable and a common level of reimbursement can be established. If a physician prescribes a medication priced . . .